Порівняльний аналіз стану судин лівої та правої верхньої кінцівки з використанням інформаційної технології морфологічного аналізу артеріальних осцилограм = Comparative analysis of vascular left and right upper extremity using information technology morphological analysis of arterial oscillograms - Vakulenko, D. V.; Vakulenko, L. A.; Pleshkanova, A. S. (Journal of Education, Health and Sport, 2015)
Vakulenko D. V., Vakulenko L. A., Pleshkanova A. S. Порівняльний аналіз стану судин лівої та правої верхньої кінцівки з використанням інформаційної технології морфологічного аналізу артеріальних осцилограм = Comparative analysis of vascular left and right upper extremity using information technology morphological analysis of arterial oscillograms. Journal of Education, Health and Sport. 2015;5(7):590-603. ISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.44550 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%287%29%3A590-603 https://pbn.nauka.gov.pl/works/690103 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.06.2015. Revised 15.07.2015. Accepted: 25.07.2015. Порівняльний аналіз стану судин лівої та правої верхньої кінцівки з використанням інформаційної технології морфологічного аналізу артеріальних осцилограм Comparative analysis of vascular left and right upper extremity using information technology morphological analysis of arterial oscillograms Д. В. Вакуленко, Л. О. Вакуленко, А. С. Плешканьова D. V. Vakulenko, L. A. Vakulenko, A. S. Pleshkanova ДВНЗ «Тернопільський державний медичний університет імені І. Я. Горбачевського МОЗ України» SHEI "Ternopil State Medical University I.Ya. Gorbachevskogo Ministry of Health of Ukraine" Summary In carrying out morphological analysis of oscillograms right and left shoulder asymmetry state of the peripheral circulation is registered in each of the 31 surveyed. Severity of asymmetries was different. It depended on the evaluated criteria and individual patients. The smallest asymmetry been registered at the study duration ripple rising parts (25%), the largest - the downlink (44% surveyed). Other criteria difference was smaller. . . However, two persons were registered significant deviations from normal parameters studied. They must be urgent in-depth examination. Keywords: arterial oscilloscopes, electronic blood pressure meters, morphological analysis of arterial waveforms. Резюме При проведенні морфологічного аналізу осцилограм правого і лівого плеча асиметрія стану периферійного кровообігу зареєстровано у кожного із 31 обстежених. Ступінь проявів асиметрій була різною. Вона залежала від оцінюваного критерію та індивідуальних особливостей обстеженого. Найменшою асиметрія реєструвалась при вивченні тривалості висхідної частин пульсації, (у 25%), найбільшою – низхідної (у 44% обстежених). За іншими критеріями різниця була меншою. . . Проте, у 2 осіб було зареєстровано значні відхилення досліджуваних параметрів від норми. Вони підлягають терміновому поглибленому обстеженню. Ключові слова: артеріальна осцилограма, електронні вимірювачі артеріального тиску, морфологічний аналіз артеріальних осцидлграм. Резюме Сравнительный анализ состояния сосудов левой и правой верхней конечности с использованием информационной технологии морфологического анализа артериальных осциллограмм. При проведении морфологического анализа артериальных осциллограмм правого и левого плеча 32 обследованных (без жалоб на состояние здоровья) асимметрия периферического кровообращения зарегистрирована у каждого из них. Степень проявления асимметрий была разной. Она зависела от критериев, подлежащих оценке и индивидуальных особенностей обследуемого. Менее выраженной она била при оценке длительности восходящей части пульсации (у 25%), наиболее – нисходящей (у 44% обследованных). По другим критериям разница оказалась меньшей. Однако, у 2 лиц зарегистрированы значительные отклонения от нормы. Они подлежат срочному углубленному обследованию. Ключевые слова: артериальная осциллография, электронные измерители артериального давления, морфологический анализ артериальных осциллограмм.